Differentiation of electronic and mobile business aspects - Čyras, Giedrius; Uturytė-Vrubliauskienė, Laura (Business, Management and Economics Engineering, 2010)
Rapid developments in mobile networks and wireless information systems nowadays are researched and adopted. Innovative business models are continually performing and could become a major benchmark in the electronic business field. Understanding them and attempting to design them are important issues. The differentiation of mobile business aspects from electronic business dimensions are a set of the parameters that set mobile business services to leading positions. One of the biggest partitive attributes between electronic mobile business applications is the working options of the user. Electronic business environment constrains the user work at the stationary position. Mobile business applications allow the user work in total mobility conditions. Also new network-based options can handle many of the services features, which can add value to mobile business services. Mobile business is the result of the electronic business and information technologies evolution. For the value adding, mobile business services should take real advantage of electronic business services, with the opportunities of creating, configuring, integrating, upgrading, troubleshooting, and maintaining new business models. A variety of mobile business service offerings that could take advantage of electronic business are presented. A treatment is suggested to add value and differentiate mobile business services, so that they continue to remain profitable.Article in Lithuanian.Elektroninio ir mobiliojo verslo lyginamoji analizė